Submission on Water Issues in Aotearoa New Zealand - Bargh, Dr Maria (Office of the High Commissioner for Human Rights, 2007)
Keywords: government; hapū; iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

Report of Matike Mai Aotearoa – The Independent Working Group on Constitutional Transformation (2018)
This report is the result of 252 hui between 2012 and 2015. The Working Group was established at a meeting of the Iwi Chairs’ Forum in 2010 with Terms of Reference: “To develop and implement a model for an inclusive Constitution for Aotearoa based on tikanga and kawa, He Whakaputanga o te Rangatiratanga o Niu
Keywords: constitutional transformation; iwi; matike mai